2013
DOI: 10.3892/ijmm.2013.1286
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 and kidney diseases (Review)

Abstract: High mobility group box 1 (HMGB1), a non-histone DNA-binding protein, regulates nucleosome function and transcription in the nuclei of all metazoans and plants. However, extracellular HMGB1, which is actively or passively released under different conditions, can act as a key inflammatory mediator through MyD88/mitogen-activated protein kinase signaling by binding to its receptors including the receptor for advanced glycation end products or Toll-like receptors. A growing body of evidence indicates that HMGB1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…HMGB1 was considered to be a novel key molecule during the IRI after KTx 6 . After it is released, HMGB1 protein can bind to its receptors that are expressed on effector cells to induce inflammation, cell proliferation, and chemotaxis, thereby acting as a bridge between the innate and adaptive immune responses 7 . HMGB1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 was considered to be a novel key molecule during the IRI after KTx 6 . After it is released, HMGB1 protein can bind to its receptors that are expressed on effector cells to induce inflammation, cell proliferation, and chemotaxis, thereby acting as a bridge between the innate and adaptive immune responses 7 . HMGB1…”
Section: Introductionmentioning
confidence: 99%
“…The signaling pathways upstream and downstream of HMGB1 remain unknown. Considering the multiple roles of HMGB1 in various pathologies, inhibition of HMGB1-mediated signaling may represent a potential effective therapeutic approach 7 . The study of…”
Section: Introductionmentioning
confidence: 99%
“…High mobility group box 1 (HMGB1), a structural chromatin-binding nuclear protein existing in almost all eukaryotic cells, can be actively secreted or passively released into extracellular regions by inflammatory or necrotic cells under specific conditions [7]. Extracellular HMGB1 acts as a pluripotent cytokine in many pathophysiological processes such as infection, injury, inflammation, obesity and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 has been demonstrated to act as a pro-inflammatory mediator and participate in human immune systems diseases (14,15). Studies indicated that innate immune cells, including macrophages and monocytes, actively secreted HMGB1 (13,16). It has been demonstrated that HMGB1 not only induces various cytokines, such as interleukin (IL)-1, IL-6 and IL-8, but also stimulates necrosis-induced inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The high mobility group box 1 protein (HMGB1), which belongs to the most evolutionarily conserved proteins in the nucleus and cytoplasm, is one of the members of high mobility group nuclear protein family (13). HMGB1 has been demonstrated to act as a pro-inflammatory mediator and participate in human immune systems diseases (14,15).…”
Section: Introductionmentioning
confidence: 99%